Review of Andrew M. Yuengert, Catholic Social Teaching in Practice: Exploring Practical Wisdom and the Virtues - Ferdinand Tablan (Journal of Moral Theology)
Review of Andrew M. Yuengert, _Catholic Social Teaching in Practice: Exploring Practical Wisdom and the Virtues_